Evaluation of Speech-Evoked Envelope Following Responses as an Objective Aided Outcome Measure: Effect of Stimulus Level, Bandwidth, and Amplification in Adults With Hearing Loss. Issue 6 (November 2015) - Easwar, Vijayalakshmi; Purcell, David W.; Aiken, Steven J.; Parsa, Vijay; Scollie, Susan D.
Abstract : Objectives: The present study evaluated a novel test paradigm based on speech-evoked envelope following responses (EFRs) as an objective aided outcome measure for individuals fitted with hearing aids. Although intended for use in infants with hearing loss, this study evaluated the paradigm in adults with hearing loss, as a precursor to further evaluation in infants. The test stimulus was a naturally male-spoken token /susa∫i/, modified to enable recording of eight individual EFRs, two from each vowel for different formants and one from each fricative. In experiment I, sensitivity of the paradigm to changes in audibility due to varying stimulus level and use of hearing aids was tested. In experiment II, sensitivity of the paradigm to changes in aided audible bandwidth was evaluated. As well, experiment II aimed to test convergent validity of the EFR paradigm by comparing the effect of bandwidth on EFRs and behavioral outcome measures of hearing aid fitting. Design: Twenty-one adult hearing aid users with mild to moderately severe sensorineural hearing loss participated in the study. To evaluate the effects of level and amplification in experiment I, the stimulus was presented at 50 and 65 dB SPL through an ER-2 insert earphone in unaided conditions and through individually verified hearing aids in aided conditions. Behavioral thresholds of EFR carriers were obtained using an ER-2 insert earphone to estimate sensation level of EFR carriers. To evaluate the effect of aided audible bandwidth in experiment II, EFRs were elicited by /susa∫i/ low-pass filtered at 1, 2, and 4 kHz and presented through the programmed hearing aid. EFRs recorded in the 65 dB SPL aided condition in experiment I represented the full bandwidth condition. EEG was recorded from the vertex to the nape of the neck over 300 sweeps. Speech discrimination using the University of Western Ontario Distinctive Feature Differences test and sound quality rating using the Multiple-Stimulus Hidden Reference and Anchor paradigm were measured in the same bandwidth conditions. Results: In experiment I, an increase in stimulus level above threshold and the use of amplification resulted in a significant increase in the number of EFRs detected per condition. At positive sensation levels, an increase in level demonstrated a significant increase in response amplitude in unaided and aided conditions. At 50 and 65 dB SPL, the use of amplification led to a significant increase in response amplitude for the majority of carriers. In experiment II, the number of EFR detections and the combined response amplitude of all eight EFRs improved with an increase in bandwidth up to 4 kHz. In contrast, behavioral measures continued to improve at wider bandwidths. Further change in EFR parameters was possibly limited by the hearing aid bandwidth. Significant positive correlations were found between EFR parameters and behavioral test scores in experiment II. Conclusions: The EFR paradigm demonstrates sensitivity to changes in audibility due to a change in stimulus level, bandwidth, and use of amplification in clinically feasible test times. The paradigm may thus have potential applications as an objective aided outcome measure. Further investigations exploring stimulus–response relationships in aided conditions and validation studies in children are warranted. Abstract : A test paradigm based on speech-evoked envelope following responses (EFRs) was evaluated for use as an objective aided outcome measure in adults with hearing loss. Audibility of the malespoken stimulus /susa∫i/ was varied by increasing the stimulus level, limiting stimulus bandwidth by low-pass filtering, and use of a hearing aid. Results suggest that the number of EFR detections and response amplitude increase with improved audibility. Sensitivity to change in audibility in clinically feasible test times suggest that the EFR paradigm may be useful as an objective aided outcome measure.Supplemental Digital Content is available in the text.